Origin of Quasi-periodic Pulsation at the Base of a Kink-unstable Jet - Mishra, Sudheer K.; Sangal, Kartika; Kayshap, Pradeep; Jelínek, Petr; Srivastava, A.K.; Rajaguru, S.P. (Institute of Physics, 2023)
We studied a blowout jet that occurred at the west limb of the Sun on 2014 August 29 using high-resolution imaging/spectroscopic observations provided by the Solar Dynamics Observatory/Atmospheric Imaging Assembly and the Interface Region Imaging Spectrograph. An inverse γ-shaped flux rope appeared before the jet-morphological indication of the onset of kink instability. The twisted field lines of the kink-unstable flux rope reconnected at its bright knot and launched the blowout jet at ≈06:30:43 UT with an average speed of 234 km s−1. Just after the launch, the northern leg of the flux rope erupted completely. The time-distance diagrams show multiple spikes or bright dots, which is the result of periodic fluctuations, i.e., quasi-periodic fluctuations (QPPs). The wavelet analysis confirms that QPPs have a dominant period of ≈3 minutes. IRIS spectra (Si iv, C ii, and Mg ii) may also indicate the occurrence of magnetic reconnection through the existence of broad and complex profiles and bidirectional flows in the jet. Further, we found that line broadening is periodic with a period of ≈3 minutes, and plasma upflow always occurs when the line width is high, i.e., multiple reconnection may produce periodic line broadening. The emission measure (EM) curves also show the same period of ≈3 minutes in different temperature bins. The images and EM show that this jet spire is mainly cool (chromospheric/transition region) rather than hot (coronal) material. Further, line broadening, intensity, and EM curves have a period of ≈3 minutes, which strongly supports the fact that multiple magnetic reconnection triggers QPPs in the blowout jet.
This paper published with affiliation IIT (BHU), Varanasi in open access mode.
Keywords: spectroscopic observations; Solar Dynamics Observatory; chromospheric; periodic fluctuations